Pengaturan Prosedur Pemungutan Pajak Kendaraan Bermotor di Kota Kupang - Ainun Blegur; Yohanes G. Tuba Helan; Rafael Rape Tupen (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Currently, the level of use of means of transportation in Indonesia is quite high, this can be found in daily life. Almost all the time we see a large number and type of vehicles popping up. This research is (1) normative research so that the data source used is a secondary data source obtained from company records, (2) empirical research so that the data source used is a primary data source obtained from the results of interviews. The results of this study show that: (1) The Regulation of Motor Vehicle Tax Collection Procedures in Kupang City is carried out based on Presidential Regulation Number 5 of 2015 concerning the Implementation of the One-Stop Manunggal Administration System by going through the stages of registration, examination of registration files, data collection, determination and control of SSPD, re-examination of SSPD and affixing of paragraphs, payment, control of SKPD, endorsement, and finally archiving, (2) The first inhibiting factor namely economic factors where there are taxpayers who have low income, high dependent burdens and unstable sources of income. The second factor is weak compliance or legal awareness of taxpayers.